Extracellular digestion in two intertidal mussels and the role played by their gut bacteria - Simon, Carol Anne (Rhodes University, Faculty of Science, Department of Zoology and Entomology, 1997)
The intertidal mussels. Perna perna and Choromytilus meridionalis co-occur on the southern coast of South Africa. Mussels ingest mixtures of bacteria. phytoplankton. zooplankton and detritus. with proportions varying according to availability. These bivalves filter similar-sized particles. which might result in interspecific competition. Carbohydrate-digesting enzymes of the mussels and their enteric bacteria. and bacteriolytic enzymes of the mussels were therefore examined to elucidate feeding ecology in these animals at an enzymatic level. Style enzymes of both species digested the storage carbohydrates amylose glycogen and laminarin, and the structural carbohydrate carboxymethyl cellulose (CMC). Differential rates of digestion of these carbohydrates suggests that Perna perna relies more on plankton (and possibly bacteria) than on detritus for food while Choromytilus meridionalis relies equally on all components of the seston. There may therefore be some degree of resource partitioning of the seston. The styles of P.perna had a lower specific enzyme activity. but higher protein content than those of C.meridionalis. P.perna could therefore release more glucose from a given concentration of substrate than C.meridionalis. The gut contents and tissue were examined microscopically to determine where the bacterial colonisation sites were. Bacteria were associated primarily with the gut contents but not the gut walls. of both species. The styles housed spirochaete bacteria (Crislispira sp), Perna perna housed large numbers of one species. while Choromytilus meridionalis had lower numbers of two species. Levels of infection differed between species and localities. Enteric (but not style) bacteria of Perna perna and Choromytilus meridionalis always digested the same carbohydrates as the mussels as well as the structural carbohydrates mannan and fucoidan. Activity was erratic on the structural compounds, carageenin and xylan, and absent on alginic acid or inulin. Activity on the storage carbohydrates by enteric bacteria from C.meridionalis was higher than by those from P.perna. This is probably related to the larger bacterial populations housed by C.meridionalis than by P.perna. Bacteriolytic activity by the digestive enzymes of Pema perna was higher than for Choromytilus. In P.perna it was due to a combination of different enzymes one of which is a true lysozyme. C.meridionalis did not produce a true lysozyme. Enzymes produced by the mussels and their enteric bacteria allow the mussels to utilise all components of the seston. Low endogenous enzyme activity by Choromytilus meridionalis, coupled with the high activity by its enteric bacteria, suggests that they rely more on bacterial activity to meet their dietary requirements than does Perna perna. The ability of enteric bacteria to digest carbohydrates which the mussels cannot indicates that the bacteria are endosymbiotic, although the sporadic nature of activity of some of the enzymes, and the fact that bacteria are associated with the gut contents, indicates that the relationship is only incidental.
Keywords: Perna -- Digestive organs; Mussels -- Digestive organs; Spirochaeta